Health Related Quality of Life and Associated Factors of Inflammatory Bowel Disease Outpatient Unit in Dr. Cipto Mangunkusumo Hospital - Muhammad Fikri Afistianto; Marcellus Simadibrata; Marcellus Simadibrata; Rudi Putranto; Rudi Putranto; Murdani Abdullah; Murdani Abdullah; Siti Setiati; Siti Setiati; Wismandari Wisnu; Wismandari Wisnu; Dono Antono; et al. (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Background: Inflammatory Bowel Disease (IBD), encompassing ulcerative colitis (UC) and Crohn's disease (CD), is an inflammatory digestive tract condition with unknown causes. Its unpredictable symptoms affect quality of life. In Indonesia, the quality of life of IBD patients remains unreported. Factors such as advanced age, long disease duration, active disease, corticosteroid use, comorbidities, unemployment, and poor sleep quality may reduce quality of life. This study aims to assess the quality of life profile of IBD patients and its associated factors.